(untitled) (Journal of Engineering, 2014)
Single phase capacitor-run induction motors (IMs) are used in various applications such as home appliances and machine tools; they are affected by the sags or swells and any fault that can lead to disturb the supply and make it produce rms voltage below or above the rated motor voltage, which is 220V. A control system is designed to regulate the output voltage of the converter irrespective to the variation of the load and within a specific range of supply voltage variation. The steady-state equivalent circuit of the Buck-Boost chopper type AC voltage regulator, as well as the analysis of this circuit are presented in this paper. Switching device for the regulator is an IGBT Module. The proposed chopper uses pulse width modulation (PWM) control technique to chop the input voltage into segments in order to guarantee rated rms voltage supplied to the load, which is capacitor-run induction motor. Proportional integral (PI) controller is used to obtain very small steady state error, stable and fast dynamic response, and robustness against variations in the line voltage. The complete system is simulated using software package, and the results are obtained to verify the proposed control method.